2016
DOI: 10.5586/asbp.3510
|View full text |Cite
|
Sign up to set email alerts
|

Identification, evaluation, and application of the genomic-SSR loci in ramie

Abstract: To provide a theoretical and practical foundation for ramie genetic analysis, simple sequence repeats (SSRs) were identified in the ramie genome and employed in this study. From the 115 369 sequences of a specific-locus amplified fragment library, a type of reduced representation library obtained by high-throughput sequencing, we identified 4774 sequences containing 5064 SSR motifs. SSRs of ramie included repeat motifs with lengths of 1 to 6 nucleotides, and the abundance of each motif type varied greatly. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Approximately 163 426 SSR loci are distributed across 17 apple chromosomes (Guan et al. ). The release of the ‘Golden Delicious’ genome sequence (Velasco et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 163 426 SSR loci are distributed across 17 apple chromosomes (Guan et al. ). The release of the ‘Golden Delicious’ genome sequence (Velasco et al.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, SSR markers are widely distributed throughout the apple genome. Approximately 163 426 SSR loci are distributed across 17 apple chromosomes (Guan et al 2011). The release of the 'Golden Delicious' genome sequence (Velasco et al 2010) has significantly simplified the search for SSR markers and the design of corresponding primers.…”
Section: Discussionmentioning
confidence: 99%
“…These studies demonstrated that the nutritive value of ramie is similar to that of alfalfa. Thus, ramie has become a new plant protein source for animal feed (Luan et al., ). In recent years, ramie has been frequently proposed as a potential phytoremediation crop due to its high heavy metal tolerance and absorption ability (Gong et al., ; Liu, Zhu, Tang, & Tang, ; Tang et al., ; Yang et al., , ).…”
Section: Introductionmentioning
confidence: 99%
“…An important reason for the high heterozygosity of Chinese chestnuts is that they are cross-pollinated plants [ 17 ]. The SSR molecular markers developed and screened in this study were highly polymorphic, and the rich genetic diversity of the participating cultivars of Chinese chestnut can be explained by the fact that the SSR molecular markers were developed based on high-quality whole-genome sequence data from Chinese chestnut, and that the genomic SSRs exhibited higher genetic diversity [ 18 ]. Another possibility is that the involved Chinese chestnut species possessed more resources and complex genetic information.…”
Section: Discussionmentioning
confidence: 99%